Economical Analysis of 3GT Traditional Fishing Vessels in The Waters of Bengkalis Island - Budhi Santoso; Jamal Jamal (LPPM Institut Teknologi Adhi Tama Surabaya (ITATS), 2021)
Bengkalis Island is the island of the capital city of Bengkalis regency, Riau province. Bengkalis Island is surrounded by the ocean so that the people who are on the edge of the coast mostly work as fishermen. Fishing boats in Bengkalis Island reach more than 2000 units. The limitations of fishing make it fishermen more difficult to get more income. There are a lot of efforts made by fishermen to improve these results including increasing engine power/speed of the ship and also changing fishing gear. To change this means increasing the operational costs of ships. For this reason, economic analysis needs to be calculated. In this study fishing boats are divided into 6 models, 3 models are distinguished based on the driving machine, namely 12 PK, 16 PK, and 24 PK while the other 3 models are distinguished based on the fishing gear, namely tansi net, kurau net, and longline. Analysis using the Net Present Value (NPV) method is knowing the model of the ship that returns the fastest capital and has the biggest advantage. The largest Net Present Value (NPV) is in Model 3 or 4 with NPV of Rp 307,091,520 and Internal Rate of Return (IRR) of 608.4%, namely yapal vessels that have 24 PK engine power and use tansi fishing gear